Factorial randomised controlled trial of glucocorticoids and combination disease modifying drugs in early rheumatoid arthritis. Issue 5 (3rd September 2007) - Choy, E H S; Smith, C M; Farewell, V; Walker, D; Hassell, A; Chau, L; Scott, D L
Abstract : Objective: Treating early active rheumatoid arthritis (RA) with disease modifying antirheumatic drug (DMARD) monotherapy achieves incomplete outcomes and intensive treatment seems preferable. As the relative benefits of combining two DMARDs, one DMARD with glucocorticoids and two DMARDs with glucocorticoids are uncertain we defined them in a factorial trial. Methods: A 2-year randomised double-blind factorial trial in patients with RA within 2 years of diagnosis treated with methotrexate studied the benefits of added ciclosporin, 9 months intensive prednisolone or both (triple therapy). The primary outcome was the number of patients with new erosions. Secondary outcomes included Larsen's x -ray scores, disability, quality of life and adverse events. Findings: 1391 patients were screened and 467 randomised. Over 2 years 132 (28%) changed therapy and 88 (19%) were lost to follow-up. The number of patients with new erosions was reduced by nearly half by adding ciclosporin or prednisolone (p = 0.01 and 0.03); both treatments reduced increases in Larsen's x -ray scores by over 2 units (p = 0.008 and 0.003). A further reduction in erosive damage was seen with combined use of both treatments. Their effects on erosive damage appeared independent. Triple therapy reduced disability and improved quality of life compared with methotrexate; ciclosporin and prednisolone acted synergistically. More patients withdrew because of adverse events with triple therapy, without an increase in serious adverse effects. Conclusions: This study confirms the existence of a "window of opportunity" in early RA, when intensive combination therapy produces sustained benefits on damage and disability. Although methotrexate–prednisolone combinations reduce erosive damage, the synergistic effect of two DMARDs is needed to improve quality of life.